Land and the City : Patterns and Processes of Urban Change. - Kivell, Philip (Geography and environment series., 1992)
In the rapidly changing sphere of urban development, land is shown to provide the basic morphological structure of the city, but also the source of economic and social power and the key to planning through examples from around the world.